THE GOVERNMENTS STRATEGY FOR RESTORING INDONESIAS TOURISM POST-COVID 19 - Widokarti, Joko (Department of Government, FISIP, Universitas Padjadjaran, 2021)
The Covid-19 pandemi has an extensive impact on the country's economy, including in the tourism sector, one of the most significant contributors to the country's foreign exchange. This study aims to provide an overview of the impact of Covid-19 on the Indonesian tourism sector and strategies made by the Government to overcome the problems and impacts of Covid-19 on Indonesian tourism. This study uses descriptive explorative qualitative methods and data collection and analysis through literature studies. Based on the analysis, it is found that the Covid-19 pandemic has indeed had a significant impact on the tourism sector and Indonesia's creative economy. One of the significance obtained is that there is an extreme decrease in Indonesia's income due to the circulation of money that does not work. However, the Government has designed policies and strategies to overcome these problems, preparing to complete the recovery of Indonesian tourism after Covid-19.gb777